Glial Cells in the Fish Retinal Nerve Fiber Layer Form Tight Junctions, Separating and Surrounding Axons - Garcia-Pradas, Lidia; Gleiser, Corinna; Wizenmann, Andrea; Wolburg, Hartwig; Mack, Andreas F. (Frontiers in Molecular Neuroscience, 2018)
In the retina of teleost fish, cell addition continues throughout life involving proliferation and axonal growth. To study how this is achieved in a fully functioning retina, we investigated the nerve fiber layer of the cichlid fish Astatotilapia burtoni for components that might regulate the extracellular environment. We hypothesized that growing axons are surrounded by different cell structures than signal conducting axons. Using immunohistochemistry and freeze fracture electron microscopy we found that the endfeet of Müller cells expressed aquaporin-4 but not in high densities as in mammals. The presence of this water channel indicates the involvement of Müller cells in water homeostasis. Remarkably, we discovered conspicuous tight junctions in the retinal nerve fiber layer. These tight junctions formed branching strands between myelin-like wrappings of ganglion cell axons that differed morphologically from any known myelin, and also an elaborate meshwork on large membrane faces between axons. We speculated that these tight junctions have additional functions than solely facilitating nerve conductance. Immunostainings against the adaptor protein ZO-1 labeled the nerve fiber layer as did antibodies against the mammalian claudin-1, 3, and 19. Performing PCR analysis, we showed expression of claudin-1, 3, 5a, 5b, 9, 11, and 19 in the fish retina, claudins that typically occur at brain barriers or myelin. We could show by immunostains for doublecortin, a marker for differentiating neurons, that new axons are not surrounded by the myelin-like wrappings but only by the endfeet of Müller cells. We hypothesize that the tight junctions in the nerve fiber layer of fish might contribute to the separation of an extracellular space around axons facilitating conductance, from a growth-promoting environment. For a functional test we applied Evans Blue dye to eye cup preparations which showed a retention of the dye in the nerve fiber layer. This indicates that these remarkable tight junctions can indeed act as a diffusion barrier.